Quais são as tendências das pesquisas fisiogerontológicas?: o caso da PUC/SP - Marques, Cristiane Maurici Gomes (2008)
What are the gerontological physical research trends? This question has led to some bibliographical research of the academic production at the Program of Post-graduated studies in Gerontology of Pontifícia Universidade Católica de São Paulo, from 2000 to July 2007, thus establishing the gerontological physical research profile. The first step to accomplishing this was mapping the former students and then gathering the abstracts of all the 171 dissertations they had done, analyzing all possible data, such as research compilation, objectives, methodology and final considerations. The softarwe Statistical Package for the Social Sciences (SPSS) was chosen for typing the closed information and statistical analysis of the data, once closed questions had been asked based on the abstracts. Each study was classified in a different thematic group created by the researcher, who then selected the 34 studies carried out by physiotherapists, which allowed her to establish the trends of gerontological physical research at PUC/SP. Most studies had investigated life quality for the elderly, longevity, clinical aspects of ageing, pathological processes, health care services and programs for the elderly. With this investigation, it was possible to clearly establish that the human being cannot be analyzed just under the biological point of view. Studies in general show the need for a humanistic and cultural approach, thus enabling a better comprehension on longevity, ageing and old age. Based on this, the creation of a discipline called Gerontology Physics is suggested in Physiotherapy bachelor courses in order to expand the understanding of Caring by the future physiotherapists